Responses of hepatic sinusoidal cells to liver ischemia–reperfusion injury - Ito, Yoshiya; Hosono, Kanako; Amano, Hideki (Frontiers in Cell and Developmental Biology, 2023)
The liver displays a remarkable regenerative capacity in response to acute liver injury. In addition to the proliferation of hepatocytes during liver regeneration, non-parenchymal cells, including liver macrophages, liver sinusoidal endothelial cells (LSECs), and hepatic stellate cells (HSCs) play critical roles in liver repair and regeneration. Liver ischemia–reperfusion injury (IRI) is a major cause of increased liver damage during liver resection, transplantation, and trauma. Impaired liver repair increases postoperative morbidity and mortality of patients who underwent liver surgery. Successful liver repair and regeneration after liver IRI requires coordinated interplay and synergic actions between hepatic resident cells and recruited cell components. However, the underlying mechanisms of liver repair after liver IRI are not well understood. Recent technological advances have revealed the heterogeneity of each liver cell component in the steady state and diseased livers. In this review, we describe the progress in the biology of liver non-parenchymal cells obtained from novel technological advances. We address the functional role of each cell component in response to liver IRI and the interactions between diverse immune repertoires and non-hematopoietic cell populations during the course of liver repair after liver IRI. We also discuss how these findings can help in the design of novel therapeutic approaches. Growing insights into the cellular interactions during liver IRI would enhance the pathology of liver IRI understanding comprehensively and further develop the strategies for improvement of liver repair.